Objetivos de desenvolvimento sustentável e o cultivo da erva-mate: estudo de caso na agroindústria Gehm - Fritz, Sinadia (2022)
Climate changes and populacional growth lead us to rethink human action upon the environment, as well as bring a light on the sustainability management. By an United Nations (UN) action in the year of 2000, supported by 191 nations, the Milenium Development Objective were stablished. After that, the 2030 Agenda was stablished, which generated the Sustainable Development Goals with the intention of carrying on a life with more coherence and quality. This investigation aims to generally verify the contribution of a small yerba mate agroindustry to the SDG. In order to do so, a qualitative and descriptive research was applied, taking the case study as guidance method, intrumentalizing data collection and information through semistructured interviews, documents and direct observation. The Gem family agroindustry is located in the municipality of Seberi RS, based on the organic growth of the yerba mate. The initial premise was to get to know the property, its history, its current structure and its intersected elements according to SDG, observing its singularity and growth. The studied agroindustry produces raw material focused on environmental regeneration and restoration, always seeking innovation that attracts environmental gains and also involves its workers in economic gains. With this study, it was possible to identify that even the small agroindustries can contribute to the ODG, as it is the case of Gem family in the yerba mate branch. Therefore, opportunities are increasing at a national and global level, where improving adaptations in the production system, and ODG implementation can lead the producer to be more competitive and present in several countries.